Introduction: special issue on weather and climate impacts in developing countries - Creti, Anna; Delacote, Philippe; Leblois, Antoine (Cambridge University Press, 2021)
Abstract Shocks related to weather variations have strong effects on developing countries’ economies. Climate change is expected to increase the occurrence and magnitude of extreme weather events such as droughts, floods or hurricanes that strongly affect agriculture and other activities. This special issue gathers literature reviews and case studies that aim to better understand heterogeneous impacts and their transmission channels, as well as to evaluate the impact of such weather shocks on developing economies, including Sub-Saharan African countries, India and Brazil.
Keywords: climate change developing countries weather shocks